THE ROLE OF SOCIAL MEDIA IN PROPAGANDA WARFARE: A STRATEGIC ANALYSIS - Rudra, Om Ji (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Social media has become a powerful tool in modern propaganda warfare, allowing state and non-state actors to manipulate public perception, spread misinformation, and conduct psychological operations. Unlike traditional propaganda, digital platforms enable real-time influence campaigns through fake news, deepfakes, and AI-driven content amplification. This paper examines the strategic use of social media in information warfare, analyzing case studies such as Russia’s disinformation in Ukraine, China’s influence in the Taiwan Strait, and ISIS’s recruitment strategies. The study explores the consequences of digital propaganda, including societal polarization, erosion of truth, and threats to democratic institutions. It also discusses countermeasures such as digital literacy programs, AI-driven misinformation detection, and international cooperation in cyber security. As social media continues to shape global conflicts, understanding its role in propaganda warfare is essential for policymakers, security agencies, and researchers. This study aims to provide insights into mitigating the risks posed by digital propaganda.